Comparative descriptive epidemiology of oral and oesophageal cancers in Europe - E. Negri; C. La Vecchia; F. Levi; S. Franceschi; L. Serra Majem; P. Boyle (European Journal of Cancer Prevention, 1996)
The two main determinants of oral and oesophageal cancer in Europe are alcohol and tobacco, and the two cancer sites show several similarities in their descriptive epidemiology. This study compares mortality from cancers of the oral cavity and oesophagus in European countries to evaluate similarities and differences. From official death certification numbers and population estimates, we obtained age-standardized rates for all ages and truncated (35-64 years). In most countries, rates for men tended to increase between 1955-59 and 1990-92 for both sites, although the increases were more marked for oral cancer. In the UK and Ireland, however, oral cancer decreased and oesophageal cancer increased, while in Finland and Iceland mortality for both sites decreased. The most striking increases were in Hungary, where the truncated rate in most recent calendar periods reached the highest levels in Europe. In France, rates for both cancers were extremely high: oral cancer increased from 1955-59 to the early 1980s, but started to decline afterwards. Mortality rates were much lower for women than men, and the correlation between the two sites was less marked. An age, period and cohort model, applied to the rates for men in selected European countries, suggested strong cohort effects for both cancers, generally more marked for oral cancer, with substantial increases in the cohorts born after 1920. The mortality rates of cancers of the oral cavity and oesophagus show several analogies, as expected from their relation to tobacco and alcohol; but some discrepancies suggest that other, less well-identified, factors may also influence their rates and trends in Europe.